Constructing ultraporous covalent organic fameworks in seconds via an organic terracotta process - Karak, S.; Kandambeth, S.; Biswal, B. P.; Sasmal, H. S.; Kumar, S.; Pachfule, P.; Banerjee, R. (Journal of the American Chemical Society, 2017)
Research on covalent organic frameworks (COFs) has recently gathered significant momentum by the virtue of their predictive design, controllable porosity, and long-range ordering. However, the lack of solvent-free and easy-to-perform synthesis processes appears to be the bottleneck toward their greener fabrication, thereby limiting their possible potential applications. To alleviate such shortcomings, we demonstrate a simple route toward the rapid synthesis of highly crystalline and ultraporous COFs in seconds using a novel salt-mediated crystallization approach. A high degree of synthetic control in interlayer stacking and layer planarity renders an ordered network with a surface area as high as 3000 m(2) g-(1). Further, this approach has been extrapolated for the continuous synthesis of COFs by means of a twin screw extruder and in situ processes of COFs into different shapes mimicking the ancient terracotta process. Finally, the regular COF beads are shown to outperform the leading zeolites in water sorption performance, with notably facile regeneration ability and structural integrity.

Selective molecular sieving in self-Standing porous covalent-Organic-framework membranes - Kandambeth, S.; Biswal, B. P.; Chaudhari, H. D.; Rout, K. C.; Kunjattu, H. S.; Mitra, S.; Karak, S.; Das, A.; Mukherjee, R.; Kharul, U. K.; Banerjee, R. (Advanced Materials, 2017)
Self-standing, flexible, continuous, and crack-free covalent-organic-framework membranes (COMs) are fabricated via a simple, scalable, and highly cost-effective methodology. The COMs show long-term durability, recyclability, and retain their structural integrity in water, organic solvents, and mineral acids. COMs are successfully used in challenging separation applications and recovery of valuable active pharmaceutical ingredients from organic solvents.

C‐F bond activation by saturated NHC: mesoionic compound formation and its unprecedented adduct with B(C6F5)3 - Pait, M.; Kundu, G.; Tothadi, S.; Karak, S.; Jain, S.; Vanka, K.; Sen, S. S. (Angewandte Chemie - International Edition, 2019)
The reaction of SIPr, [1,3‐bis(2,6‐diisopropylphenyl)‐imidazolin‐2‐ylidene] (1), with C6F6 led to the formation of an unprecedented mesoionic compound (2). The formation of 2 is made accessible by deprotonation of the SIPr backbone with simultaneous elimination of HF. The C−F bond para to the imidazolium ring in 2 is only of 1.258(4) Å, which is the one of the shortest structurally authenticated C−F bonds known to date. The liberation of HF during the reaction is unequivocally proved by the addition of one more equivalent of SIPr, which leads to the imidazolium salt with the HF2− anion. To functionalize 2, the latter reacted with B(C6F5)3 to give an unusual donor–acceptor compound, where the fluoride atom from the C6F5 moiety coordinates to B(C6F5)3 and the carbanion moiety remains unaffected. Such coordination susceptibility of the fluoride atom of a nonmetallic system to a main‐group Lewis acid (Fnon‐metal→BR3) is quite unprecedented.
Keywords: C-F activation; carbanions; N-heterocyclic carbenes; structure elucidation; Ylides